Inborn Errors of Immunity With Immune Dysregulation: From Bench to Bedside - Delmonte, Ottavia Maria; Castagnoli, Riccardo; Calzoni, Enrica; Notarangelo, Luigi Daniele (Frontiers in Pediatrics, 2019)
Primary immune deficiencies (PIDs) are genetic disorders with broad clinical manifestations, ranging from increased susceptibility to infections to significant immune dysregulation, often leading to multiple autoimmune phenomena, lymphoproliferation and malignancy. The treatment is challenging as it requires careful balancing of immunosuppression in subjects at increased risk of infections. Recently, the improved ability to define PID pathophysiology at the molecular level has set the basis for the development of targeted therapeutic interventions. Such a “precision medicine” approach is mainly bases on the use of available small molecules and biologics to target a specific cell function. In this article, we summarize the clinical and laboratory features of various recently described PIDs associated with immune dysregulation and hyperinflammation and present mechanism-based therapeutic approaches that have been implemented in these disorders.